Application of omics technology in the storage and transportation of agricultural products - Bai, Lu; Zhang, Zixuan; Peng, XIn; Gao, Zhiwei; Zhao, Yan; Liang, Kehong (Frontiers in Sustainable Food Systems, 2023)
Agricultural products may deteriorate due to various reasons during storage and transportation, resulting in serious losses. However, the mechanism of deterioration is complex, and many mechanisms are currently unclear. In recent years, the rapid development of omics technologies, such as genomics, proteomics, transcriptomics, and metabolomics, has led to breakthroughs in exploring the mechanism of product quality changes during the storage and transportation of agricultural products, and also help to understand molecular mechanisms. By using omics technology to gain a deeper understanding of the changes in agricultural products during storage and transportation, more efficient, environmentally friendly, and resource saving storage and transportation methods can be developed, providing a research foundation for the sustainability of China's agricultural food system. In addition, research on omics technology has provided theoretical support for screening more suitable storage methods and transportation conditions. This review presents the potential application omics technologies in agricultural product storage and transportation. The application examples of omics technology in the storage and transportation process of agricultural products were discussed. Finally, the prospects indicate that omics technology has unlimited potential.